Role of Media on National Issues during Musharraf’s Era: A Critical Review - Naz, Sadia; Shaukat, Bushra; Naz, Fara (Annals of Human and Social Sciences, 2024)
The world now feels like a hamlet because of the vast amount of information and electronic media. There are no longer any restrictions on the travel of information, news, and events to any location on the planet. Dictators have typically closely monitored the media to suppress criticism. Authoritarian governments in dictatorships frequently heavily repress the mainstream media to avoid crossing their perceived limits of acceptability. Musharaf took responsibility for the freedom of the media revolution in Pakistan. Pakistan Electronic Media Regulation Authority granted unprecedented power to halt broadcast transmissions, close offices, seize equipment, revoke licenses, and increase fines for violations. There was a challenge for Musharraf to address the media after the revolution. Media visuals have the power to shape emotions, thoughts, and worldviews. The role of mass media in society is not only to educate and inform the public but also to shape national identity. The aim of this article is to analysis the role of media on national issues. This research utilized a secondary source of data collection. Examining the dictatorial rule in Pakistan; this article highlights the significance of media regulations and legislation in the country.